The Plebeian Republic: The Huanta Rebellion and the Making of the Peruvian State, 1820-1850 by Cecilia Méndez Gastelumendi - Igue Tamaki, José Luis (2006)
Review of The Plebeian Republic: The Huanta Rebellion and the Making of the Peruvian State, 1820-1850